PROFILE OF COMMUNICATION SKILLS IN BIOLOGY FOR XI GRADE STUDENTS OF â€œYâ€ SENIOR HIGH SCHOOL IN MADIUN REGENCY - Sasmito, Anggit; Suciati, Suciati; Mariadi, Mariadi (Unnes Science Education Journal, 2017)
Communication skills is one of the important competences which needs to be trained continuously to compete in ASEAN Economic Community (AEC). Communication skills can be trained in education. In Indonesia, this skills is one of ten future needed competences for every student. The purpose of this research is to analyze the communication skills of students in biology class for XI grade of Y Senior High School in Madiun Regency. This research used descriptive method. The method of collecting data in this research was using non-test approach by analysis of learning implementation using non-participatory observation and documentation in pictures, audio, and video. The measurement of students; communication was obtained through scoring instrument with twelve indicators: 1) various data description, 2) descriptive relation data, 3) various meaning of data, 4) exploring the content of material with different ideas, 5) data validity, 6) differentiate data and conclusion, 7) clarifying questions, 8) ensuring friends’ question, 9) responding friends’ statement, 10) separating ideas, 11) revising opinion from friends’ input, 12) concluding interesting conclusion. The analysis of data used quantitative descriptive approach. The result of the analysis showed that from twelve indicators, only two indicators appears from students’ communication skills in learning biology. Those were indicator 8) 41.2% and indicator 9) 58.8%. Based on the analysis, it can be concluded that students’ communication skills in biology class from XI graders of Y Senior High School in Madiun Regency was relatively low. Based on the result of the research, there should be a development of learning design which can improve students’ communication skills.